TEORİ VE UYGULAMADA KAMBİYO SENEDİNİN ARKA YÜZÜNE LEHTARIN CİROSUNDAN ÖNCE ATILAN İMZA (ŞEKLİNDEKİ GARANTİ CİROSU) - (:unkn) unknown (My University, 2017)
Emre yazılı kambiyo senetlerinde, borcun ödeneceğini garanti etmek adınaçeşitli yöntemler kullanılmaktadır. Her biri farklı hukuki sonuçlara ulaşan bu yöntemlerin başlıcaları, kanunda da açıkça düzenlenmiş olan aval ile garanti cirosudur. Garanticirosu; teminat vereni ciro silsilesine ekleme veya çalışmamızın asıl konusu olan, senedin arkasına ciro zinciri dışına yalın (tek) imza atmak suretiyle yapılır. Kambiyo senediarkasındaki ciro zinciri dışında kalan bu yalın imzanın; hukuki niteliği, sorumluluk doğurup doğurmadığı ve ödemede bulunan garanti cirantasının başvuru hakkına sahip olupolmayacağı, gerek yabancı gerek Türk hukuk öğreti ve uygulamasında hayli tartışmalıdır. Yargıtay’ın çoğunluk içtihatları teminat cirosunun hukuki varlığını ve ekonomikdeğerini göz ardı etmektedir. Bu çalışmada hedeflenen; uygulamada aval yerine kullanılmasına çok rastlanan, özellikle senedin arkasında ve lehtarın cirosundan imza şeklindeki garanti cirosuna ilişkin hukuki esasları ortaya koymak, diğer bir anlatımla bu imzaların neden garanti/teminat cirosu olarak geçerli kabul edilmesi gerektiğini, yani sorumluluk doğuracağını, ciro zincirini koparmayacağını ve ödemede bulunan bu imza sahibinin başvuru hakkına sahip olacağını tespit ve tayin etmektir.

For bills payable to order, various methods are used in order to ensure the payment. Within these methods, each of which results in a different legal outcome, primary ones are the Aval and Guarantee endorsement. Guarantee endorsement can be made either by attaching the warrantor into the chain of endorsements or by signing on the reverse side of the bill and outside the chain of endorsements with no other indications. The legal nature of this simple signature that stands outside the chain of endorsements, and whether this signature brings any responsibility to the signee and also whether the signee will have a right to recourse in case of a payment, are highly debated both in Turkish and foreign law doctrines and practices. Most decisions of the Turkish Court of Cassation ignore the legal existence and economic value of the guarantee endorsement. The present study aims to suggest the legal grounds for guarantee endorsement, which has been frequently used in practice in the place of Aval, especially by signing on the reverse side of the bill above the payee’s endorsement. In other words this study aims to ascertain and to determine why these signatures should be deemed valid as guarantee endorsement and therefore bring responsibility without harming the chain of endorsements and eventually why the signee who makes payment should have a right to recourse.
Guarantee Endorsement in Theory and Practice as Signing on the Reverse Side of the Bill Before the Payee’s Endorsement
Keywords: Hukuk